(untitled) (Research, Society and Development, 2022)
Introduction: One of the ways that have been observed to reduce musculoskeletal fatigue is the use of protocols for the application of light sources (photobiomodulation) such as low-intensity laser and LED (Light Emitting Diode). Work involving photobiomodulation has shown promising results in strength performance or reduction of muscle fatigue. At the cellular level, photobiomodulation can modulate fibroblasts proliferation, the fixation and synthesis of collagen and procollagen, promote angiogenesis and improving energy metabolism in mitochondria. Compared with laser devices, LED has several advantages, such as being smaller, lighter, lower cost, and easier for operation. Objective: The present work objective is to verify if irradiation with LED device (650 nm and 860 nm) in muscle cells C2C12 modify the viability, morphology and cytoskeleton components. Methodology: C2C12 cells line (ATCC CRL - 1772) were cultured in 25 cm2 bottles at 37ºC under 5% CO2 in DMEM. The cells were irradiated with the light-emitting diodes (LED) device, Sportllux Ultra that consists of 84 LEDs, each individual LED has 8 mW of power, emitting in 660±20 nm (42 LEDs) and 850±20 nm (42 LEDs), and covering an area (A) of 120 cm2. The power density of delivered light was 5,6 mW/cm2, and the exposure time was 10 minutes, totalizing the fluence of 3,4 J/cm2. Viability assay was performed where the cells were incubated with 100 µL of Crystal Violet (CV) solution and mitochondrial activity assay was evaluated by the colorimetric MTT assay. Nucleus (DAPI) and Cytoskeleton (Rhodamine Phalloidin) fluorescence assay was performed to study the cytoskeleton based on the change in the actin filaments. Results: Our results demonstrate that the synergism of LED irradiation (660nm and 850nm) induced the proliferation of C2C12 cells. The light-emitting diode (LED) device, Sportllux Ultra has a significant effect on C2C12 cell culture. Mitochondrial activity and cell viability showed a significative increase in their activities after irradiation. The microscopy fluorescence observations showed an alignment of cytoskeletal components of C2C12 cells after irradiation. Conclusion: The application of irradiation with the Sportlux Ultra LED device stimulated an increase of energy by mitochondrial activity assay, number of cells by cell viability assay and alignment of cytoskeleton components by fluorescence assay in C2C12 line cells. Our results suggest that organizated cytoskeletal actin filaments normally contribute to cell survival and that induced major cell changes in the cytoskeleton that result in cell shape change. These results suggest that the Sport Lux Ultra LED device can help in the repair of tissue injuries and to collaborate to increase of performance in athletes in a faster way.